2015
DOI: 10.1074/mcp.m114.045609
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of Human Fibroblasts with I1061T Mutation in Niemann–Pick C1 (NPC1) Protein Provides Insights into the Disease Pathogenesis*

Abstract: Niemann-Pick type C (NPC) disease is a fatal neurodegenerative disorder characterized by the accumulation of unesterified cholesterol in the late endosomal/lysosomal compartments. Mutations in the NPC1 protein are implicated in 95% of patients with NPC disease. The most prevalent mutation is the missense mutation I1061T that occurs in ϳ15-20% of the disease alleles. In our study, an isobaric labeling-based quantitative analysis of proteome of NPC1I1061T primary fibroblasts when compared with wild-type cells id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 74 publications
5
52
0
Order By: Relevance
“…The most frequent mutation, I1061T, present in 15-20% of all disease alleles (27,28), is in the α5 helix of the CTD (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent mutation, I1061T, present in 15-20% of all disease alleles (27,28), is in the α5 helix of the CTD (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported secreted lysosomal enzyme alterations in both the mouse model and in NPC1 patients where many enzymes associated with drug metabolism have been identified that may have reduced activities in NPC1 patients . Cologna et al., identified potential markers of neuroinflammation in the cerebral cortex in both the mouse model as well as in NPC1 patients . Most recently, primary patient fibroblasts have been evaluated in large‐scale differential proteomics studies to reveal protein changes as a result of treatment with 2‐hydroxypropyl‐beta‐cyclodextrin or histone deacetylase inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these data, it has also been shown that pharmacological treatments that lead to upregulation of NPC1 variant expression, including ryanodine receptor antagonists [17], treatment with oxysterols that bind to and stabilize NPC1 [18], reduced expression of TMEM97 [19], and HDAC inhibitors [20], partially abrogate the NPC1-I1061T phenotype in heterologous cell and patient fibroblast models. These findings highlight that modulation of the local folding and signaling environment can facilitate disease correction [21][22][23][24].…”
Section: Introductionmentioning
confidence: 85%